An Insight into Structural and Mechanical Properties of Ideal‐Networked Poly(Ethylene Glycol)–Peptide Hydrogels from Molecular Dynamics Simulations. Issue 3 (9th January 2020) - Rukmani, Shalini J.; Anstine, Dylan M.; Munasinghe, Aravinda; Colina, Coray M.
Abstract: Simulations of local structure and interactions in stimuli‐responsive hydrogel networks at atomistic resolution has the capability to compliment experimental efforts by providing insight into current soft materials design challenges. This work simulates ideal hexafunctional networks of poly(ethylene glycol) (PEG)‐diacrylate (PEGDA) and PEG–peptide hydrogels with two enzyme‐responsive peptide sequences, Gly‐Leu‐Lys (GLK) and Gly‐Pro‐Gln‐Gly‐Ile‐Phe‐Gly‐Gln‐Lys (GPQGIFGQK), using molecular dynamics (MD) simulations at water contents from 84% to 90%. This presents the first atomistic MD study of a PEG–peptide hydrogel. The mesh sizes obtained are compared to common swelling theories and the available micropore space for diffusion is compared to the sizes of a family of matrix metalloproteinases (MMPs) to predict size‐based exclusion. The effects of interactions between PEG, peptide, and water on the chemical environment surrounding the cleaving site of peptides are investigated by examining partial radial distribution functions and solvent accessible surface areas. The chemical environment around the peptide sequence is found to be more hydrophobic in PEG‐9‐peptide hydrogels, thereby favoring cleavage by the hydrophobic binding pocket of MMPs. Furthermore, the mechanical moduli of the hydrogels is also examined, and an increase with the incorporation of peptide sequences and a general decrease with increasing water concentration is observed. Abstract : Molecular simulations of enzyme‐responsive poly(ethylene glycol) (PEG)–peptide hydrogels can provide insight into the network structure and local interactions between polymer, peptide, and water molecules at the atomistic level. This work characterizes mesh sizes, dynamic micropore size distributions, local interactions between PEG, peptide and water molecules, and tensile modulus to guide the design of matrix metalloproteinase (MMP)‐responsive PEG–peptide hydrogels.